Agricultura caificada no Sudoeste de Goiás: do bônus econômico ao ônus sócio-ambiental - Ribeiro, Dinalva Donizete (2005)
This paper focus on the industrially integrated agriculture from the southeast of Goiás. This kind of agriculture is locally called caificada , adjective derived from CAIs ( Complexos Agroindustriais Agroindustrial Complexes). Based on the hypotheses that the economic growth generated by this kind of agriculture does not come with a development process, this research was carried out with the aim of demonstrating that this very type of agriculture is a generater of wealth and a booster of the regional economic growth, but that happens at a cost in expropriation, exploitation, exclusion, segregation, and damage to natural resources. Therefore, the current agricultural exploration model in the region is dealt with here as unbearable, due to the fact that, beside not representing development (only growth), it also means a serious threat to natural resources, that is, to nature health including human health. The research and daily life reveal that there is a contradiction, denotating the incompatibility between the econimic growth indexes and the social development indexes. In the larger grain-producer southeast counties, one might verify poverty and misery contrasting with luxury and magnificence. The economic bonus generated by the caificada agriculture is a privilege of an elite, costing to the majority of the population the social and environmental price originated from the agricultural practice developed there.